An Analysis of Types and Functions of Taboo Words in Hot Fuzz Movie - Tungkagi, Shabina Azzabilla; Djohan, Rita Sutjiati (STIBA IEC JAKARTA, 2024)
In daily lives, a person can adapt speech patterns, vocabulary, and accents to fit with social surroundings. From the formal language used in workplace to the informal language spoken with friends and relatives. The informal spoken form of language, particularly viewed as being of lower social rank than standard language is called vernacular. Vernacular represents the everyday language spoken by people, including slangs and taboo words that develop over time. The purpose of this research is to find the types and functions of taboo words in Hot Fuzz movie. The researcher used a qualitative descriptive method. The researcher used two theories of taboo words from Edwin Battistella (2005) to analyze the types and Timothy Jay to analyze the functions (1992). The data in the research was taken from the dialogues of the Hot Fuzz movie. The total data of taboo words found in the movie are 65 data. The researcher found all four categories of types of taboo words, they are 8 Epithets, 16 Profanity, 14 Vulgarity, and 27 Obscenity. The researcher found all five categories of functions of taboo words, they are 20 Anger and/or Frustration, 17 Descriptive – Evaluative, 10 Joking, 9 Surprise, and 9 Sarcastic Irony or Insults.